Technology use in Swedish reindeer husbandry through a social lens - Andersson, E.; Keskitalo, E. C. H. (Polar geography (1995), 2017)
Rationalizing production more effectively, technological developments and innovations also have effects on, for example, skills, knowledge and social relations, that connect the specific technique to large processes and rationalities. In the conflict between user rights and ownership rights in northern Sweden, the introduction of new techniques within reindeer husbandry is studied on a local and embodied level. Through observations and interviews, the tension between empowerment and control in their implementation is further explored by utilizing a labor process theoretical framework. The results illustrate a shift in the definition of skills and knowledge, in relation to the use of GPS and GIS, that reshape, reorganize, restructure and embody the labor process of reindeer husbandry and spatial, temporal and ecological relations. Through its production of subjective conditions and dependence, the disciplinary logic of these techniques contributes to shape and enact governable spaces and subjects within the context. Operating as technologies of government, the techniques emphasize the responsibilities of the reindeer herding community and shape their participation, by reinforcing the demand for certain kind of subjectivities and accountability - governmental rationales that contribute to a technologicalization and depoliticizing of policy and conflict managing.